Connecting teens with technology at the library - Czarnecki, Kelly Nicole, 1974- (The teen librarian bookshelf, 2021)
"Connecting Teens with Technology at the Library presents a balanced view of the often complex relationship between teenagers and their technology. The authors share more than a dozen full lesson plans for technology-based programs, scalable for any library budget, that will help the reader to engage with their teenaged patrons"--